2019
DOI: 10.1080/10942912.2019.1634099
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing volatiles in brown rice vinegar by headspace solid-phase microextraction (SPME)–Arrow: Optimizing the extraction conditions and comparisons with conventional SPME

Abstract: The ability to readily determine the composition of brown rice vinegar is important for quality assurance purposes. To that end, solid-phase microextraction (SPME)-Arrow method was optimized for the determination of volatile organic compounds (VOCs) from brown rice vinegar. Compared to traditional SPME fibers, SPME-Arrow has a larger sorbent-phase volume and is more durable. The SPME-Arrow conditions, including coating material, extraction temperature, extraction time, and NaCl concentration, were examined, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…SPME Arrows are also covered with a larger volume (6–20 times) of the sorbent phases than SPME fibers, indicating a higher sample capacity [ 23 , 24 , 25 ]. Therefore, SPME Arrow extracts are more efficient and have better reproducibility than SPME fibers and allow for more volatile compounds to be extracted and analyzed in food [ 23 , 24 , 25 ]. Since the development of the SPME Arrow, studies on the analysis of harmful components, such as polycyclic aromatic hydrocarbons in water and volatile amines in wastewater, have been carried out [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…SPME Arrows are also covered with a larger volume (6–20 times) of the sorbent phases than SPME fibers, indicating a higher sample capacity [ 23 , 24 , 25 ]. Therefore, SPME Arrow extracts are more efficient and have better reproducibility than SPME fibers and allow for more volatile compounds to be extracted and analyzed in food [ 23 , 24 , 25 ]. Since the development of the SPME Arrow, studies on the analysis of harmful components, such as polycyclic aromatic hydrocarbons in water and volatile amines in wastewater, have been carried out [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are not as many publications on SPME Arrow in food analysis, as compared to traditional SPME fibers [8]. However, in the past couple of years, several applications have spanned the analysis of diverse matrices including fish and rice [52,53]. For instance, Song and coworkers compared carboxen/polydimethylsiloxane (CAR/PDMS) SPME sorbents in the fiber format to the arrow format for the HS extraction of volatiles present in salt-fermented sand lance fish sauce [53].…”
Section: Food Analysismentioning
confidence: 99%
“…SPME-arrow fiber is a new device, which has 6–20 times larger than the sorbent phase of traditional SPME fiber and shows more than 10 times the sensitivities and extraction efficacies [ 20 ]. Until now, SPME-arrow fiber has been employed for the determination of volatiles of various food products, such as brown rice vinegar [ 21 ], Korean salt–fermented fish sauce [ 20 ], soy sauce [ 22 ], and milk [ 23 ]. In these studies, SPME-arrow showed higher extraction performance, such as more kinds of compounds extracted, larger extraction amount, and better reproducibility.…”
Section: Introductionmentioning
confidence: 99%